Inclusion of Intra- and Interspecific Facilitation Expands the Theoretical Framework for Seagrass Restoration - Zhang, Y. Stacy; Gittman, Rachel K.; Donaher, Sarah E.; Trackenberg, Stacy N.; van der Heide, T.; Silliman, Brian R. (Frontiers in Marine Science, 2021)
Restoration is increasingly utilized as a strategy to stymie the loss of coastal habitats. Coastal habitat restoration has predominantly emphasized designs that minimize physical stress and competition. As evidence of the pervasiveness of this approach, we conducted a global survey of seagrass restorationers and found a strong affinity for stress-avoidant designs with adult shoots in dispersed rather than aggregated configurations. To test the alternative hypothesis that including positive interactions can enhance restoration success, we experimentally incorporated: (i) interspecific facilitation (clam additions) into seed sowing, and (ii) both intra- and interspecific facilitation (planting a single-large versus multiple-small patches and adding clams) into shoot planting. Clam additions to seeds significantly enhanced plant biomass and patch size; and nutrient analysis suggested the causative mechanism was clam enhancement of available nitrogen. In contrast, adult outplant growth was enhanced by intra- but not inter-specific facilitation. Dispersed configurations consistently declined, whereas large-intact patches, which had the same initial biomass as dispersed plots, increased in patch area and doubled in shoot density. These results demonstrate that expanding restoration strategies to include positive interactions with respect to seagrass ontogeny has the capability to switch the trajectory of restoration from failure to success.